THE ANALYSIS OF NON PERFORMING FINANCING (NPF) DETERMINANTS ON INDONESIAN ISLAMIC BANKING (PERIOD FROM JANUARY 2003 - MARCH 2013) - Nasih, Mohammad (Journal of Innovation in Business and Economics, 2013)
This study aims to analyze the factors affecting the Non Performing Financing (NPF) Sharia banking in Indonesia.The factors examined are Economic Performance (EK), Total Financing (FIN), Financing Rate (FR), Dummy Global Financial Crisis (D07) and Inflation Rate (INF).The method used is Cointegration Test.The data used are monthly data.The study time period is from January 2003 to March 2013. Based on the results of statistical analysis it show that each of independent variables, is significantly influence the growth of NPF (non-performing financing) Sharia banking in Indonesia.Results of the study give the implication that the Islamic banking should be correctly applying the precautionary and prudential principles, in providing financing to customers to avoid high NPF in Islamic banking. And the Government as the highest authority of the banking institution, expected to support the financing of Islamic banking sector of the economy by establishing the independent agency, which helped the bank to assess the eligibility of prospective business who proposed financing on Islamic banking